Duration of amantadine benefit on dyskinesia of severe Parkinson's disease. Issue 1 (5th January 2004) - Thomas, A; Iacono, D; Luciano, A L; Armellino, K; Di Iorio, A; Onofrj, M
Abstract : Background: Recent short-term studies suggested that amantadine (Ama) might ameliorate dyskinesia in patients with Parkinson's disease. A double-blind study programmed over 12 months was designed to assess the duration of the antidyskinetic effect of amantadine on levodopa induced dyskinesia. Methods: 40 patients treated for 7.5 (2.2) years with levodopa (729.3 (199.4) mg/day) and dopaminoagonists, having peak dose or dyphasic dyskinesia with or without pain, were assessed with the Unified Parkinson's Disease Rating Scale subscale IV, Items 32–34, the Dyskinesia Rating Scale and Investigator Global Assessment. Twenty patients received amantadine chloridrate (100 mg) and 20 received a placebo. The Ama or placebo could be withdrawn when scores indicated worsening of dyskinesia, after agreement with the patient. Results: After 15 days of amantadine treatment there was a reduction by 45% in the total dyskinesia scores. All patients in the placebo group were withdrawn in 1–3 months and all patients in the Ama group were withdrawn in 3–8 months (p = 0.01, p<0.001). Ama withdrawal induced a rebound with increase of dyskinesia by 10–20% in 11 patients. Conclusion: 300 mg amantadine reduces dyskinesia in Parkinson's disease by approximately 45% but the benefit lasted less than eight months.